The practice of oral feeding after total laryngectomy by Brazilian head and neck surgeons - Johanna Benali; Tareck Ayad; Fabio Pupo Ceccon; Carlos Chiesa-Estomba; Jerome R. Lechien; Mateus Morais Aires; Leonardo Haddad; Gerrit Viljoen; Nicolas Fakhry (Brazilian Journal of Otorhinolaryngology, 2025)
Objective: To evaluate the initiation of oral feeding in patients following TL by a group of Brazilian head and neck surgeons. Methods: Online survey – 75 responders from Brazil. Results: 40.5% of the respondents introduced water and 41.9% of them introduced liquid diets between days 7 and 9 after TL without surgical complications or previous radiotherapy. Semi-solid feeds were started between days 10 and 14 in 47.3% of the patients and a free diet was begun after day 15 in 79.7% of them. There was statistically significant difference in the initiation of liquid feeds between different groups of TL patients, with earlier initiation in TL patients who had not undergone prior radio(chemo)therapy (p = 0.01419), with even greater differences when complex closure of the pharynx was needed (p = 0.00001), but not regarding the moment of a free diet introduction. Conclusion: Most respondents in this Brazilian cohort prefer to wait at least 7-days before beginning oral feeding after TL without previous radiotherapy or surgical complications, with a significant number of respondents postponing feeds in patients who had undergone salvage TL and pharyngolaryngectomy. Level of evidence: Level IV.